Verbal and Non-Verbal Signs on Webtoon Seasons of Blossom - Permataswari, Anak Agung Asrimas (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2024)
This undergraduate thesis is entitled Verbal and Non-Verbal Signs on Webtoon Seasons of Blossom. This undergraduate thesis mainly focuses on analysing verbal and non-verbal signs on webtoon Seasons of Blossom. It was aimed to identify the signifier and signified of verbal and non-verbal signs, and explain the relationship between the verbal and non-verbal signs to determine a meaningful event on webtoon Seasons of Blossom. The theory by Saussure is used to analyze the signifiers and signified of the verbal and non-verbal signs as the first problem. The theory by McCloud is used to analyze the second problem about relationship between words and pictures. Qualitative method are used in this undergraduate thesis. The source of data is the 28th episode with the sub-title Bomi’s Flower (28) by using documentation method. The data were presented in the form of pictures and table. The result of analysis shows that the signifiers and the signified are found in the verbal and non-verbal signs on webtoon Seasons of Blossom. The verbal and non-verbal signs are work well to support each other in delivering the idea. The relationship between verbal and non-verbal signs are also determine a meaningful event in the analysis. Keyword : Verbal Sign, Non-Verbal Signs, Webtoon